Nutritional Status Collection Using Height And Weight Indicators At Posyandu Latalanyir Based On The Internet Of Things - Remi Awang, Irene; Pingky Alfa Ray Leo Lede; Hawu Yogia Pradana Uly (Yayasan Kita Menulis, 2024)
This research aims to develop a nutritional status data collection system at Posyandu Latalanyir using height and weight indicators based on the Internet of Things (IoT). This system is designed to simplify the process of measuring and collecting data on the nutritional status of toddlers, as well as increasing the accuracy and efficiency of data processing. The approach used involves using an ultrasonic sensor to measure body height, an HX711 load cell sensor to measure body weight, and an ESP8266 module to send data to the Blynk platform. The collected data will be processed to calculate Body Mass Index (BMI) and sent to the Blynk application for real-time monitoring. The results of this research show that the system developed can measure height and weight accurately, as well as provide nutritional status data that can be easily accessed by health workers at posyandu. The conclusion of this research is that the IoT system developed is effective in improving the quality of nutritional status data collection in posyandu, as well as providing significant benefits in monitoring the nutritional development of toddlers.